2019
DOI: 10.1111/jog.13980
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aerobic glycolysis enhances the anti‐tumor efficacy of Zoptarelin Doxorubicin in triple‐negative breast cancer cells

Abstract: Aim A characteristic of cancer cells including triple‐negative breast cancers (TNBC) is an increased aerobic glycolysis for ATP production representing a selective therapeutic target. More than 70% of TNBC express gonadotropin‐releasing hormone receptors (GnRH‐R). These receptors can be used for targeted chemotherapy with cytotoxic GnRH agonists such as Zoptarelin Doxorubicin, in which doxorubicin is covalently linked to [D‐Lys6]GnRH. In this study, we have analyzed whether inhibition of aerobic glycolysis can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Many studies have reported that as a glucose analogue, 2DG could inhibit glycolysis through inhibiting hexokinase and play a direct or auxiliary role in antitumor. 10,28,42 Confusingly, the combination of 2DG and DHA had neither synergy nor antagonism on the expression of PKM2 and GLUT1 in our study ( Figure 5). The potential mechanisms of DHA and 2DG on glycolysis might be different.…”
Section: Dovepressmentioning
confidence: 49%
“…Many studies have reported that as a glucose analogue, 2DG could inhibit glycolysis through inhibiting hexokinase and play a direct or auxiliary role in antitumor. 10,28,42 Confusingly, the combination of 2DG and DHA had neither synergy nor antagonism on the expression of PKM2 and GLUT1 in our study ( Figure 5). The potential mechanisms of DHA and 2DG on glycolysis might be different.…”
Section: Dovepressmentioning
confidence: 49%
“…Furthermore, a wide range of factors that might serve as therapeutic targets suppressed breast cancer by regulating aerobic glycolysis, including betulinic acid, 31 miRNA‐186‐3p, 32 tumor‐derived macrophages, 33 and zoptarelin doxorubicin. 34 Our current study showed that LINC01605 promoted breast cancer by targeting LDHA, which is also a crucial enzyme in aerobic glycolysis. Although this is the first report of the role of LINC01605 in breast cancer by regulating aerobic glycolysis, noncoding RNAs have been extensively explored and proven as key mediators of aerobic glycolysis in breast cancer for a long time.…”
Section: Discussionmentioning
confidence: 62%
“…For example, it was shown that exposure of TNBC cells to high glucose concentrations induces proliferation and abrogates the apoptotic effects induced by the drug metformin [150]. Other studies demonstrated that combined treatments, inducing the metabolic switch from glycolysis to OXPHOS, increases the sensitivity of TNBC cells to mitochondrial respiratory complex I inhibitors [151]; whereas inhibition of aerobic glycolysis enhances antitumor efficacy of Zoptarelin Doxorubicin, a cytotoxic agonist of gonadotropin-releasing hormone receptor (GnRH-R), expressed in more than 70% of TNBC tumors [152]. Altogether, these studies indicate that combinational treatment, including energy metabolism-targeting agents, may represent a therapeutic strategy for aggressive TNBC treatment.…”
Section: Erβ Effect On the Bioenergetics Of Tnbcmentioning
confidence: 99%